Modeled and Observed Bedrock Displacements in North‐East Greenland Using Refined Estimates of Present‐Day Ice‐Mass Changes and Densified GNSS Measurements. Issue 4 (4th April 2021) - Kappelsberger, Maria T.; Strößenreuther, Undine; Scheinert, Mirko; Horwath, Martin; Groh, Andreas; Knöfel, Christoph; Lunz, Susanne; Khan, Shfaqat A.
Abstract: Models of the glacial‐isostatic adjustment (GIA) to past ice‐mass changes exhibit large differences in north‐east Greenland owing to insufficient knowledge about glacial history and Earth rheology. The GIA uncertainties feed back to uncertainties in present‐day mass‐balance estimates from satellite gravimetry. Geodetic Global Navigation Satellite System (GNSS) measurements allow to directly observe displacement of bedrock. We present results from repeated and continuous GNSS measurements conducted within five measurement campaigns between 2008 and 2017. We used the observed uplift rates to validate different GIA models in conjunction with estimates of the elastic response of the solid Earth to present‐day ice‐mass changes. To determine present‐day ice‐mass changes and the associated elastic deformations, we combined satellite altimetry data from CryoSat‐2 with satellite gravimetry data from the Gravity Recovery and Climate Experiment for the entire Greenland Ice Sheet (GrIS) and included peripheral glaciers and ice caps. The different GIA models were consistently used in all processing steps. The GNSS measurements in north‐east Greenland revealed uplift rates in the range of 2.8 to 8.9 mm yr −1 . The comparison of the total displacement predicted by GIA and elastic modeling with the GNSS‐based displacement clearly favors GIA models that show low rates (0.7–4.4 mm yr −1 at the GNSS sites) against GIA models with higher rates of up to 8.3 mm yr −1 . The correction due to the favored GIA model in north‐east Greenland results in an ice‐mass loss of 233 ± 43 Gt yr −1 for the GrIS including peripheral glaciers over the period July 2010 to June 2017. Key Points: Geodetic Global Navigation Satellite System (GNSS) measurements at bedrock sites in north‐east Greenland revealed uplift rates in the range of 2.8 to 8.9 mm yr −1 Elastic predictions were derived from ice‐mass change estimates combining Gravity Recovery and Climate Experiment and CryoSat‐2 data and including peripheral glaciers Models predicting low glacial‐isostatic adjustment rates (0.7–4.4 mm yr −1 at the GNSS sites) were confirmed